Dynamics of intestinal permeability indicators in patients with metabolic-associated fatty liver disease in combination with type 2 diabetes - Pavlovskyi , Leonid; Chernyavskyi , Volodymyr; Tyshchenko , Victoria; Gvozdetska, Lesya (The Ukrainian Scientific Medical Youth Journal, 2023)
it is known that increased permeability of the intestinal wall affects the course and progression of fatty liver disease more often in patients with metabolically associated fatty liver disease (MAFLD) than in healthy individuals. In this regard, the aim of our work was to investigate the effect of probiotics and an intestinal antibiotic - rifaximin on the total level of zonulin, occludin, interleukin-6 (IL-6) and the lactulose-mannitol ratio in patients with MAFLD in combination with type 2 diabetes. The study involved 60 patients with MAFLD in combination with type 2 diabetes, who were divided into two groups. Patients in both groups were treated with metformin at a dose of 500 mg 2 times a day and a hypocaloric diet with a daily deficit of 400-500 kcal in combination with 30-minute walking 5 times a week. In addition, the patients of the second group additionally took a combined synbiotic (S.boulardii, L.acidophilus, L.rhamnosus, inulin) 1 capsule 2 times a day for 3 months and rifaximin 200 mg 2 tablets 3 times a day for 14 days. The control group included 20 healthy volunteers. Using the ELISA method, the total level of zonulin, occludin and IL-6 in the plasma of both groups was determined before and 3 months after treatment. The level of intestinal permeability was studied using the lactulose-mannitol test. The levels of zonulin, occludin, IL-6, and lactulose-mannitol ratio were significantly increased in patients with MAFLD combined with type 2 DM compared to the control group (p < 0.001). In patients who took probiotics and rifaximin, the levels of zonulin, occludin, IL-6, and lactulose-mannitol ratio were significantly reduced compared to patients who did not take them (p < 0.001). The effectiveness of probiotic therapy and rifaximin in improving the state of intestinal epithelial permeability has been confirmed in patients with MAFLD in combination with type 2 diabetes.